Patient satisfaction with chronic disease care and its associated factors in primary health care facilities in Johannesburg, South Africa - Kagura, Juliana; Khamisa, Natasha; Matsena Zingoni, Zvifadzo; Dulaze, Neo; Awuku-Larbi, Yaw; Tshuma, Ndumiso (Frontiers in Health Services, 2023)
This study examined the predictors affecting chronic disease patients' levels of satisfaction with care in Johannesburg, South Africa. Methods: A cross-sectional study was conducted among 2429 chronic disease patients at 80 primary healthcare facilities in Johannesburg, South Africa. Factor analysis and logistic regression approaches were utilised Results: The majority of chronic disease patients 65.5% (n=1592) were aged 18-30 years. The odds of being satisfied increased by 28% (AOR=1.28,95%CI:1.07-1.53), 45% (AOR=1.45,95%CI:1.2-1.75), 34% (AOR=1.34,95%CI:1.13-1.59) and 4.31 (95%CI:3.55-5.23) for every score increase in the factors like improving values and attitudes, cleanliness of clinic safe and effective care and availability of medicine, respectively. Conclusions: Adjustment of existing frameworks for addressing context-specific improvement of patient experiences is recommended to ensure healthcare quality and service utilization for better chronic disease outcomes.